Study of Biostimulation Effect in Burn Healing with Suspension of Freshly Isolated and Cryopreserved Mesenchymal Embryonic Cells - Revenko, E. B.; Petrenko, A. Yu.; Goncharuk, E. I.; Volkova, N. A.; Petrenko, T. F.; Volina, V. V. (Problems of Cryobiology and Cryomedicine, 2004)
The influence of both freshly isolated and cryopreserved mesenchymal embryonic cells (MEC) on reparative process activity in a burn wound was studied. Obtained results have shown the viable freshly isolated either cryopreserved embryonic cells are capable of accelerating the wound defect re-epithelization processes. No rough scar during the skin recovery process and cosmetic cicatrix tissue formation are peculiar for their effect.